Conformational Analysis (Semi Empirical PM3) and Electronic Properties of Functionalized Oligo(hexylpyrroles) - O. A. Odunola; B. Semire (E-Journal of Chemistry)
A semi empirical analysis of functionalized 3-hexylpyrroles [3XHP, where X= Br, NH2, SH, CN, COOH, CONC(CH3)2 and N(CH3)2] having functional group attached to the hexyl substituent up to four monomeric units in head-tail-head-tail regioselectivity was carried out. The energy band gap obtained at PM3 level showed that oligomers with 3BHP present lowest energy band gap. The energy band gap changed with the functional group attached to hexyl substitutents, which affect the molecular properties related to the electronic conductivity.